Characteristics of Madariaga and Venezuelan Equine Encephalitis Virus Infections, Panama - Luis Felipe Rivera; Carlos Lezcano-Coba; Josefrancisco Galué; Xacdiel Rodriguez; Yelissa Juarez; William M. de Souza; Zeuz Capitan-Barrios; Anayansi Valderrama; Leyda Abrego; Hector Cedeño; Carmela Jackman; Jesse J. Waggoner; et al. (Emerging Infectious Diseases)
Madariaga virus (MADV) and Venezuelan equine encephalitis virus (VEEV) are emerging arboviruses affecting rural and remote areas of Latin America. However, clinical and epidemiologic reports are limited, and outbreaks are occurring at an increasing frequency. We addressed the data gap by analyzing all available clinical and epidemiologic data of MADV and VEEV infections recorded since 1961 in Panama. A total of 168 human alphavirus encephalitis cases were detected in Panama during 1961‒2023. We described the clinical signs and symptoms and epidemiologic characteristics of those cases, and also explored signs and symptoms as potential predictors of encephalitic alphavirus infection compared with those of other arbovirus infections occurring in the region. Our results highlight the challenges for the clinical diagnosis of alphavirus disease in endemic regions with overlapping circulation of multiple arboviruses.